Giant Metrewave Radio Telescope unveils steep-spectrum antique filaments in the galaxy cluster Abell 725. Issue 2 (18th October 2021) - Pandge, M B; Kale, Ruta; Dabhade, Pratik; Mahato, Mousumi; Raychaudhury, Somak
ABSTRACT: We present original Giant Metrewave Radio Telescope (GMRT) radio observations of the galaxy cluster Abell 725, at a redshift ( z ) of 0.09, along with other archival observations. Our GMRT maps reveal two steep-spectrum diffuse filaments in the cluster, along with a previously reported arc-like structure, and a wide-angle-tail (WAT) radio source associated with the brightest cluster galaxy (BCG) at the periphery of the cluster. The bent morphology of the WAT indicates that its jets have been swept back by the dynamic pressure resulting from the motion of the BCG through the surrounding intracluster medium. The BCG associated with the WAT hosts a black hole whose mass we estimate to be 1.4 $\ ±\ 0.4 × 10^{9}\, \rm M_{\odot }$ . We observe a 2 arcmin (195 kpc in projection) offset between the BCG and the X-ray centroid of the galaxy cluster, which, along with other dynamic features, indicates the cluster's early stage of evolution. The WAT radio galaxy, the arc, and the filaments have spectral indices $α _{612}^{240}= -0.46\ ±\ 0.15$, −0.8 ± 0.3, and (−1.13 ± 0.48, −1.40 ± 0.50), respectively. The WAT and the arc are connected structures, while the filaments are detached from them, but are found to be along the trail of the WAT. Based on the morphology of the components, and the progressive steepening of the components from the core of the WAT to the filaments, we propose that this system is a radio galaxy with trailing antique filaments.